FONOLOGI BAHASA MELAYU DIALEK MELAWI - Noviani, Riska; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research is motivated that the community of BMDM speakers in Hilir City, Suka Maju Village, are native speakers. The problems in this research are phonetics in BMDM, phonemic in BMDM, and the forms of learning implementation. The purpose of this study is to describe the phonetic aspects of BMDM, the phonemic aspects of BMDM, and the implementation of learning. The method used is descriptive method in the form of qualitative. data collection tools namely recorder and write. The phonetic aspects of BMDM vocal sounds are six phonemes, the consonant sounds of BMDM are eighteen phonemes, the phonemic aspects of BMDM vocal phonemes are six. Consonant phonemes are seventeen sounds namely /b/, /p/, /t/, /d/, /c/, /k/, /l/, /m/, /g/, /Ê”/, /É²/ , /Å‹/, /j/, /y/, /w/, /n/, /s/, and /É£/. Vowels and consonants in sound inventory, phoneme verification, phoneme distribution, and phoneme realization are located at the beginning, middle and end of words. Diftong BMDM namely [ai], [oi], [au], and [it]. The BMDM syllable structure is (1) KVK, (2) V-KV, V-KVK, KV-VK, KV-KV, KV-KVV, KV-KVK, KV-KVKV, KVK-KV, AND KVK-KVK, 3) KV-KV-KV, KV-KV-KVK, KVK-KV-KV, KVK-KV-KVK, and KV-KVK-KVK. Implementation of learning is to recognize, pronounce and arrange words in local languages.Â Keywords: Dialect Melawi, Malay, Phonology